Optimized scheme for efficient and scalable key management in IEEE 802.16e-based networks - Sadeghi, Mohammad Mehdi Gilanian (2015)
The computer industry has defined the IEEE 802.16 family of standards that will enable mobile devices to access a broadband network as an alternative to digital subscriber line (DSL) technology. Based on this standard, WiMAX which stands for worldwide interoperability for microwave access, was introduced by an industry consortium called WiMAX Forum, to offer a broadband wireless access to a plethora of mobile devices such as lap top, smart phones, and potentially any other network of devices. Subsequently, Mobile WiMAX was developed based on IEEE802.16e to support mobility where mobile devices can then roam from one coverage area to the next and remain connected. As the mobile devices join and leave a network, security measures must be taken to ensure the safety of the network against unauthorized usage by encryption and key management. IEEE 802.16e uses multicast and broadcast service (MBS) as an efficient mechanism to distribute the same data concurrently to multiple mobile stations (MSs) through one Base Station. To generate, update and distribute the keys for secure communication over IEEE 802.16e, the MBS applies Multicast and Broadcast Rekeying Algorithm (MBRA) as a basic key management algorithm. The main performance parameters of group key management schemes are typically communications, computation and storage cost as well as scalability and energy efficiency. This thesis focuses on improving group key management performance in IEEE 802.16e. In general, there is a trade-off among the communications, computation and storage costs of key management scheme. The aim is to enhance the group key management performance by providing a good trade-off among the communications, computation and storage costs. In addition, the proposed scheme should guarantee network scalability and consumes less energy upon rekeying process.First, a new key management scheme called Scalable and Efficient Key Management Protocol (SEKMP) is proposed. It is built on two tree data structures that organize the MSs into subgroups which enable it to manage the group keys effectively. One of the trees is a binary tree data structure and the other is a B-tree data structure. The aim of SEKMP is to seek a balance between various performance parameters. Next, an enhanced version of the proposed Scalable and Efficient Key Management Protocol called extended SEKMP (E-SEKMP) is developed based on SEKMP. E-SEKMP works by arranging the MSs into three main groupings based on their duration of stay in the cell, which in turn depends on the speeds of the respective MSs. Simulation results show that SEKMP achieves a better balance among the performance parameters compared against the other schemes, while E-SEKMP shows reduced communications costs and energy consumptions. In terms of communications costs, the proposed scheme shows 77.41% improvement in comparison to MBRA, and an average of 47.87% improvement over ELAPSE in all modes, while in energy consumptions, the proposed scheme consumes less energy with an average of 38.27% improvement over that of ELAPSE. In terms of scalability, the proposed scheme shows 94.18% improvement compared to MBRA and 61.15% compared to ELAPSE.